THE CREATING A GREEN VILLAGE ATMOSPHERE (FREE) COVID-19 IN WADUNG VILLAGE, JENU DISTRICT, TUBAN DISTRICT - Hyan Oktodia Basuki; Mei Widyawati; Muhammad Fahrul Arifin (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
The Tuban Government has made to prevent the spread of Covid-19, but the main obstacle is the level of public understanding of the importance health protocols. The people of Tuban Regency have varying levels of engagement in responding to the protocol. Jenu District has a large area, and diverse communities and is the centre of industry in Tuban Regency. This is what makes the people in Jenu District very diverse, both local people and immigrants. In particular, people who live around the industrial environment, need to get special attention related to their understanding of Covid-19.The methods that are responsible to the community need to be improved to prevent the transmission of the Covid-19 case. Through this health education program, it is hoped to increase the public's awareness and understanding of the importance of implementing health protocol to create a Green Village or Covid-19 Free.This program was successful with the support of the community and they follow every program that is carried out in an orderly and enthusiastic manner. In addition to health education activities, this program also assists in food staples, masks, hand sanitizers, and the construction of hand washing facilities in several public facilities in Wadung Village. Keywords: Health Protocol, Covid-19, Green Village, and Community.